Anonymous Opt-Out HIV and hepatitis C screening at a syringe services program in Florida - Heather Henderson; Jason Wilson; Bernice McCoy; Megan Sarmento; Asa Oxner (Harm Reduction Journal)
Abstract This paper outlines the implementation of opt-out HIV and Hepatitis C (HCV) screening at a syringe services program (SSP) in Florida, highlighting its effectiveness in reducing the transmission of these infectious diseases. Historically, many SSPs have utilized opt-in testing models, which require participants to actively choose testing and often result in low participation rates. Recognizing the need for a more effective approach and to comply with Florida’s regulatory requirements under the Infectious Disease Elimination Act, we transitioned to an opt-out testing model at our SSP. This model integrates routine, anonymous, and voluntary testing into standard care, normalizing the process and reducing stigma associated with infectious disease screening. Initially, our policy tied testing to access to specific services, including syringe exchange, to meet compliance with Florida Department of Health mandates. However, after feedback from participants, staff, and community members, we revised our approach to allow all participants to access all services, regardless of their decision to participate in testing. Importantly, this policy change did not decrease testing rates, with only 6 out of 226 new enrollments (3%) opting out since the implementation of opt-out screening. By fostering a trusting, non-coercive environment and normalizing screening as part of routine care, we achieved high rates of participation while maintaining participant autonomy. Since transitioning to an opt-out model, we have conducted nearly 3,000 HIV and HCV tests, with seropositivity rates of 3.8% and 54%, respectively. These efforts have facilitated early detection, rapid linkage to care, and reduced transmission within the community. Our findings underscore the importance of comprehensive, repeat testing in high-risk populations and demonstrate the potential for opt-out models to serve as a scalable framework for SSPs nationwide. This approach not only fulfills regulatory and public health objectives but also strengthens the role of SSPs as critical interventions in combating HIV and HCV transmission.